Factores que influyen en la identidad cultural en los estudiantes de secundaria en la I.E. N° 60087 Lucille Gagne Pellerin, Santa Clotilde 2022 - Chang Reategui, Manuel Alejandro (2023)
The objective of the research was to determine the factors that influence cultural identity in high school students at I.E. N°60087 Lucille Gagne Pellerin, Santa Clotilde, in the year 2022. The type of research was descriptive-quantitative and the method used was correlational-transectional, since the information was collected at the same time to describe relationships between cultural identity and the following factors: globalization, social and personal. The study population consisted of all the students of the I.E. N°60087 Lucille Gagne Pellerin, Santa Clotilde, enrolled in the year 2022, which were a total of 643 students and a non-probabilistic intentional sample was used where the 2nd grade of secondary school was chosen for the collection of information and a total of 117 students were used. The techniques used considering the size of the sample were: the survey, where the students could jointly indicate their appreciation of the factors under study and the interview where the teacher studied the cultural identity, as instruments the questionnaire was used to obtain the results of the indicators of the three factors and the interview form to identify how the cultural identity is developed. As a result of the application of the Kendall Tau-b correlation, it was obtained that there is influence of the Globalization, Social and Personal Factor in Cultural Identity.